Prognostic and clinicopathological roles of long non-coding RNA XIST in human cancers: a meta-analysis - Shen, Liang; Li, Changzhong; Liu, Ming; Wei, Deying; Chang, Qin; Cui, Jing (Translational Cancer Research, 2018)
Background: Mounting evidence has indicated that long non-coding RNA X-inactive specific transcript (XIST) could lead to cancer development and progression. This paper explored the association between XIST levels and clinical outcomes of cancer patients through a meta-analysis. Methods: We performed a systematic search through several databases, such as PubMed, EMBASE, Web of Science, Cochrane Library, CNKI, and WanFang, in order to collect cohort studies that reported XIST expression in various cancers. Two investigators independently screened documents, extracted data and evaluated the risk of bias of the included studies. Results: Eventually, data from 841 patients were selected from 12 studies. Our results suggested that there was a significant correlation between high level of XIST and poor overall survival (HR =1.791, 95% CI: 1.030–3.114, P